Deficiency of the pyruvate dehydrogenase component in pyruvate dehydrogenase complex-deficient human fibroblasts. Immunological identification. - Ho, L (1986)
A previously reported deficiency of "total" pyruvate dehydrogenase complex activity is further characterized. Dihydrolipoyl transacetylase (E2) and lipoamide dehydrogenase (E3) activities in the patient's fibroblasts were normal. Pyruvate dehydrogenase activity (E1) was 33% of that in fibroblasts from an age-matched control. The amounts of each of the components of pyruvate dehydrogenase complex were analyzed using an immunoblot technique and specific antibodies. Levels of components E2 and E3 were the same in fibroblasts from the patient and control, confirming the activity measurements. However, the levels of E1 alpha and E1 beta were reduced markedly in fibroblasts from the patient. Thus, impairment in the pyruvate dehydrogenase complex activity was due to a reduction in the amount of the E1 component of the complex.